Citra Merek dan Harga Terhadap Keputusan Pembelian Air Minum Dalam Kemasan (AMDK) Merek AQUA - Dede Nurkomalasari (Digital Economic, Management and Accounting Knowledge Development (DEMAnD), 2021)
The aim of this research is to detect brand image and price that can have an impact on purchasing decisions for bottled drinking water (AMDK) of the Aqua brand (a case study on consumers of Aqua brand bottled drinking water in Sukabumi City). The associative research method used by researchers, the population size is unknown, after being calculated by the Cohcran formula, a sample of 97 respondents is produced. The sampling technique is by chance sampling technique. Methods of analysis include data quality test, analysis prerequisite test, multiple linear regression analysis test, coefficient of determination analysis and hypothesis testing using the SPSS version 24 statistical program. The results of brand image and price simultaneously have a significant effect on purchasing decisions.